Landmarks of Vocational Education and Training in the European Union - Sorin Petrică ANGHELUȚĂ; Carmen Valentina RĂDULESCU; Florina BRAN; Dumitru Alexandru BODISLAV; Svetlana Platagea GOMBOS (Communications of International Proceedings, 2021)
In order to monitor progress in the field of vocational education and training, new objectives have been set at European Union level through the new strategic framework. It is desirable that, for periods of learning abroad, the European area of education should allow for the automatic recognition of learning outcomes as well as qualifications. The article examines the extent to which targets for strategic objectives are met. The aim of European cooperation in the field of education and training is to create a European area of education. Thus, the participants in the training processes have the possibility to look for a job, as well as the possibility to be able to continue their studies throughout their lives. Even though the COVID-19 pandemic has affected all areas, including education, it is important to continue the learning and teaching processes. The activities assigned to the study must not be interrupted. In order to increase the quality of the educational process, it is necessary for the field of education and vocational training to benefit from efficient and effective investments. Comparative analyzes regarding the strategic objectives are presented.
Keywords: European Union; education; training